Prevalence of childhood parasites in the Municipal Early Childhood Education Center (CMEI) in São Pedro do Ivaí, state of Paraná (Research, Society and Development, 2025)
Enteroparasitosis is one of the causes of mortality among children, being triggered by helminths and/or protozoa, as in this age group, children have a developing immune system, therefore, they present the most serious symptoms. The present research aims to verify the presence of parasites in stool samples from children aged 1 to 3 years, enrolled in a CMEI in the municipality of São Pedro do Ivaí- PR. The present investigation analyzed nineteen stool samples that were collected from children aged between 1 and 3 years old and analyzed using microscopic techniques. After analysis using the Hoffman method, it was found that 53% of the samples were positive for intestinal parasites, including Ancylostoma duodenale (31.6%), Giardia lamblia (21.1%) and Entamoeba coli (5.3%). Enteroparasitosis mainly causes malabsorption, chronic diarrhea, anemia, malnutrition and learning difficulties in children, requiring investigation and treatment.